Morphology and molecular dynamics investigation of low molecular weight PDMS adsorbed onto Stöber, fumed, and sol-gel silica nanoparticles. (18th July 2018) - Klonos, P.; Bolbukh, Yu.; Koutsiara, C.S.; Zafeiris, K.; Kalogeri, O.D.; Sternik, D.; Deryło–Marczewska, A.; Tertykh, V.; Pissis, P.
Abstract: Morphology, glass transition and molecular dynamics of polydimethylsiloxane (PDMS) adsorbed onto three types of silica nanoparticles, namely Stöber, fumed-pyrogenic, and silica gel, were studied employing scanning electron microscopy (SEM), isothermal nitrogen adsorption–desorption, calorimetry (DSC) and broadband dielectric spectroscopy (BDS) techniques. The initial Stöber particles (specific surface area S BET ∼240 m 2 /g) form a quite loose silica network with mainly textural pores of ∼12 nm in size. Fumed silica ( S BET ∼260 m 2 /g) demonstrates denser aggregation and increased textural porosity (∼11 nm), while silica gel ( S BET ∼850 m 2 /g) exhibits tremendous intraparticle porosity (tubular-like pores of ∼6 nm). On adsorption of PDMS (at ∼20 and ∼30 wt%), the glass transition temperature ( T g ) decreases as compared to the bulk, while the glass transition step broadens. Results suggest loosened molecular packing of the polymer chains accompanied by a broadening of the range of relaxation times in the composites as compared to the neat polymer. On the other hand, the heat capacity step at glass transition is significantly suppressed in the composites, suggesting the formation of a rigid polymer fraction (RAF) at the interfaces with nanoparticles due to strong physical interaction (hydrogen bonding). RAF increases in the order Stöber < fumed (A300) < silica gel, this increase following that of S BET, in agreement with results in previous work on silica/PDMS systems. Next to the segmental dynamics ( α relaxation) of the bulk-like polymer related to the glass transition, BDS allowed the detection of a separate segmental-like relaxation of the polymer in the interfacial silica-PDMS zone. In terms of timescale the interfacial relaxation is almost identical for Stöber and A300, and slightly faster for silica gel. Comparison of the results of the present work with previous results obtained with similar nanocomposites based on low molecular weight PDMS and silica, provides additional support to recently proposed ' S BET –interfacial dynamics' and 'chain packing–polymer dynamics' correlations. Graphical abstract: Image 1 Highlights: Specific surface area of initial silicas Stöber (240 m 2 /g)<fumed (260 m 2 /g)<silica gel (850 m 2 /g). In silica/PDMS composites T g decreases and range of relaxation times increases. Indications for rigid amorphous fraction (RAF) in the interfacial layer by DSC. Retarded mobility of the interfacial polymer by BDS, α int relaxation next to α of the bulk. RAF and interfacial dynamics governed by specific surface area ( S BET ).